A chlorosilicate cyan long afterglow luminescent material and preparation method thereof

By adopting the chemical structure of Sr8-m-nSi4O12Cl8:Eum, Rn and low temperature calcining technology, the problems of short afterglow time and low luminous brightness of chlorosilicate long afterglow materials are solved, and the combination of long afterglow time and high luminous brightness is achieved. And the synthesis conditions are simple.

CN116875302BActive Publication Date: 2025-02-14NORTHWEST NORMAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310877714.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2025-02-14
Estimated Expiration
2043-07-18

AI Technical Summary

Technical Problem

The existing chlorosilicate long afterglow materials have problems such as short afterglow time, low luminous brightness and complex synthesis conditions.

Method used

Using the chemical structure of Sr8-m-nSi4O12Cl8:Eum, Rn, a chlorosilicate cyan long afterglow luminescence material with long afterglow time and high luminescence brightness was prepared through low temperature calcination and appropriate auxiliary activator regulation.

Benefits of technology

The long afterglow time is extended and the luminous brightness is improved, and the synthesis conditions are relatively simple and the calcination temperature is low. The material can emit light continuously under dark conditions for about 8 hours, with an initial brightness of 0.1927cd/m2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116875302B_ABST
    Figure CN116875302B_ABST
Patent Text Reader

Abstract

The invention discloses a chlorosilicate cyan long afterglow luminescent material and a preparation method thereof. The chemical expression of the luminescent material is Sr 8‑m‑n SiO 12 Cl8:Eu m ,R n . According to the stoichiometric ratio of each element in the chemical expression, each raw material is weighed, mixed, and then an appropriate amount of ethanol is added and ground. After mixing, it is calcined in a high-temperature tube furnace with a reducing atmosphere, and then ground again after cooling in the furnace to obtain a chlorosilicate cyan long afterglow luminescent material. The luminescent center of the luminescent material obtained comes from Eu 2+ , trivalent rare earth ion La 3+ 、Ce 3+ As auxiliary activating ions, the luminous intensity of the long afterglow luminescent material is enhanced and the luminous time is increased. After irradiation with ultraviolet light for 10 minutes, the light source is removed and the afterglow of about 8 hours can still be observed. At the same time, it has the excellent chemical stability and thermal stability of silicate materials. In addition, the preparation method of the present invention is simple, pollution-free and low-cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photoluminescent materials and relates to a long afterglow luminescent material, in particular to a chlorosilicate cyan long afterglow luminescent material and a preparation method thereof. Background Art

[0002] Long afterglow luminescent materials refer to a type of luminescent material that can continue to emit light for a period of time (several seconds or even days) after being excited by certain excitation sources (such as X-rays, ultraviolet light, visible light, etc.). The wavelength range of afterglow emission can range from ultraviolet light to infrared light. Due to the special luminescent properties of long afterglow luminescent materials and the absence of toxic heavy metals, they are widely used in night displays, safety signs, road traffic signs, biosensors and bioimaging. At the same time, with the rapid development of science and technology, it has also been widely studied in the field of information technology anti-counterfeiting.

[0003] As for the long afterglow matrix, the first generation of long afterglow materials is a sulfide system based on ZnS and CaS, but this system has problems such as easy generation of a large amount of harmful gases during the production process, low afterglow brightness, and short luminescence time. Subsequently, the aluminate system was widely studied as the second generation of long afterglow materials, among which SrAl4O7: Eu 2+ , Dy 3+ and Sr4Al 14 O 25 : Eu 2+ , Dy 3+ It is commercialized due to its extremely excellent luminescence. However, the aluminate system has poor water resistance and cannot be used in many humid conditions. In order to solve this problem, silicate systems with high thermal stability, stable chemical properties, relatively good water resistance and simple synthesis conditions have been developed one after another.

[0004] Patent application "Europium and ytterbium co-doped silicate green light long afterglow material and its preparation method and application" (application number 202210288037.3, published on August 30, 2022) discloses a Sr 1.99-2x Eu 0 .01 Yb x Na x Al 2-y Ga y SiO7 green long afterglow phosphor, 3+ and Al 3+ Regulation, enhance the afterglow intensity, and prolong the afterglow time; the patent "A pyrosilicate long afterglow luminescent material and preparation method" (patent application number 201711058128.3, authorization announcement date 2020.03.31) discloses a pyrosilicate long afterglow luminescent material Sr 6-x-y Al2Si6O 21 :xEu2+ ,yR. This makes the silicate long afterglow luminescent material have new absorption wavelength and luminescent color.

[0005] In the prior art, chlorosilicate is relatively rare as the matrix of long afterglow materials, and there are problems such as short afterglow time, low luminous brightness, and relatively complex synthesis conditions. For example, the reported chlorosilicate long afterglow phosphor Ca8Zn(SiO4)4Cl2:Eu 2+ The afterglow time is only 200s. 2+ Long afterglow phosphor, the afterglow time is 3h, but the preparation process is complicated, and it takes two steps of high-temperature solid phase method to get the desired product. And the synthesis temperature is high, and the reaction needs to be carried out at 1200℃. Summary of the invention

[0006] The invention aims to provide a chlorosilicate cyan long afterglow phosphor with a long afterglow time, which is suitable for the fields of safety fire protection and emergency lighting indication.

[0007] Another object of the present invention is to provide a method for preparing the above-mentioned long afterglow luminescent material with simple synthesis conditions.

[0008] To achieve the above object, the technical solution adopted by the present invention is: a chlorosilicate cyan long afterglow luminescent material, the chemical structure of which is: Sr 8-m-n SiO 12 Cl8:Eu m , R n ;

[0009] Wherein, R is one of La, Tm, and Nd; or R is a combination of Gd and Dy; or R is a combination of Ho and Er;

[0010] 0.001≤m≤0.4, 0.001≤n≤0.4.

[0011] Another technical solution adopted by the present invention is: a method for preparing the above-mentioned chlorosilicate cyan long afterglow luminescent material, which is carried out according to the following steps:

[0012] 1) According to the chemical expression Sr 8-m-n SiO 12 Cl8:Eu m , R n The stoichiometric ratios of the chemical elements in the mixture are as follows:

[0013] SrCO3 or SrO;

[0014] SiO2 or H2SiO3;

[0015] NH4Cl or SrCl2

[0016] Eu2O3;

[0017] One of La2O3, Tm2O3, Nd2O3; or Gd2O3 and Dy2O3; or Ho2O3 and Er2O3;

[0018] Transfer all the raw materials to an agate mortar, add an appropriate amount of ethanol and grind them thoroughly (30 min), mix them evenly, and obtain a raw material mixture;

[0019] 2) placing the raw material mixture in an alumina crucible, moving it to a high-temperature tube furnace, introducing a reducing atmosphere and sintering it at 800-1100° C. for 3-6 hours, and cooling it to room temperature along with the furnace to obtain a calcined product;

[0020] There are three types of reducing atmospheres: the first is ammonia (NH3); the second is a mixed gas composed of 5-25% hydrogen (H2) and 95-75% nitrogen (N2) by volume; the third is a mixed gas composed of 5-25% carbon monoxide (CO) and 95-75% nitrogen (N2) by volume.

[0021] 3) Grind the calcined product to obtain chlorosilicate blue long afterglow luminescent material.

[0022] The present invention has the following advantages:

[0023] 1. The present invention uses Sr8Si4O 12 Cl8 is the matrix, Eu 2+ As the luminescence activator, the trivalent rare earth ion La 3+ 、Ce 3+ As auxiliary activators, calcination at low temperature enhances the luminescence performance of long afterglow phosphors. Compared with aluminates and silicates, the former have higher calcination temperatures and are easy to deliquesce; the latter have high preparation requirements and average afterglow performance. In contrast, this chlorosilicate has the advantages of simple synthesis conditions, excellent luminescence performance and stable chemical properties.

[0024] 2. Sintering can be completed using an ordinary tubular furnace. Compared with common aluminates and silicates, the sintering temperature is about 200~400℃ lower.

[0025] 3. So far, about Sr 8-m-n SiO 12 Cl8:Eu m , R nThe long afterglow luminescence performance has not been reported, and cyan long afterglow luminescent materials under dark conditions are also relatively rare. Compared with other chlorosilicate long afterglow luminescent materials, this sample has high photoluminescence brightness and long afterglow duration. After being irradiated with a 254nm ultraviolet lamp for 10 minutes, the light source is removed and the afterglow can still be observed for about 8 hours. The initial brightness of the afterglow is 0.1927cd / m 2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is the XRD spectrum of the cyan long afterglow luminescent material prepared in Examples 1 to 6.

[0027] Figure 2 The cyan long afterglow luminescent material Sr prepared in Example 1 7.96 SiO 12 Cl8: Eu 0.01 , Ce 0.03 Afterglow decay curve.

[0028] Figure 3 The cyan long afterglow luminescent material Sr prepared in Example 1 7.96 SiO 12 Cl8: Eu 0.01 , Ce 0.03 Thermoluminescence curve of .

[0029] Figure 4 It is the emission spectrum diagram of the cyan long afterglow luminescent material prepared in Examples 1 to 6.

[0030] Figure 5 The cyan long afterglow luminescent material Sr prepared in Example 3 7.939 SiO 12 Cl8: Eu 0.03 , Gd 0.006 , Dy 0.025 Afterglow decay curve.

[0031] Figure 6 The cyan long afterglow luminescent material Sr obtained in Example 4 7.972 SiO 12 Cl8: Eu 0.02 , Nd 0.008 Thermoluminescence curve of .

[0032] Figure 7 The cyan long afterglow luminescent material Sr obtained in Example 5 7.91 SiO 12 Cl8: Eu 0.04 , La 0.05 Afterglow decay curve. DETAILED DESCRIPTION

[0033] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0034] Example 1

[0035] According to the chemical formula Sr 7.96 SiO 12 Cl8: Eu 0.01 , Ce 0.03 1.1751 g of SrCO3, 0.2403 g of SiO2, 0.4279 g of NH4Cl, 0.0018 g of Eu2O3 and 0.0052 g of CeO2 were weighed respectively, all the raw materials were transferred to a mortar, an appropriate amount of alcohol was added, ground and mixed evenly to obtain a raw material mixture; the raw material mixture was placed in an alumina crucible, moved to a high-temperature tube furnace, and introduced into a reducing atmosphere composed of 5% H2 and 95% N2 by volume, calcined at 900°C for 4 hours, cooled to room temperature with the furnace, ground, and a chlorosilicate cyan long afterglow luminescent material (Sr 7.96 SiO 12 Cl8: Eu 0.01 , Ce 0.03 ).

[0036] The XRD spectrum of the cyan long afterglow luminescent material prepared in Example 1 is as follows: Figure 1 As shown in the figure, it can be seen that the cyan long afterglow luminescent material is a very good single-phase sample, and no obvious impurity peak appears. The chromaticity coordinates of the cyan long afterglow luminescent material obtained in Example 1 are calculated using the CIE chromaticity diagram: x=0.1308, y=0.2687, which is located in the cyan luminescent area. In the case of complete darkness, the lowest brightness that the human eye can observe is 0.00032cd / m 2 The afterglow decay time of the cyan long afterglow luminescent material obtained in Example 1 can be maintained at this brightness for about 8 hours (after irradiation with a 254nm UV lamp for 10 minutes, the light source is removed), and the initial afterglow brightness is 0.1927cd / m 2 ,like Figure 2 shown. Figure 3 This is a thermoluminescence curve of the cyan long afterglow luminescent material obtained in Example 1. It can be seen from the figure that there are two traps, with peaks at 77°C and 272°C respectively. It is generally believed that the thermoluminescence peak slightly above room temperature, that is, in the range of 50-120°C, is most conducive to the generation of afterglow at room temperature. Therefore, the trap at 77°C is very beneficial to afterglow.

[0037] Example 2

[0038] According to the chemical formula Sr 7.785 SiO 12 Cl8: Eu0.015 , Tm 0.2 The raw materials were transferred into a mortar, and an appropriate amount of alcohol was added, ground and mixed to obtain a raw material mixture. The raw material mixture was placed in an alumina crucible, transferred to a high-temperature tube furnace, and introduced into a reducing atmosphere composed of 10% CO and 90% N2 by volume. The mixture was calcined at 1000°C for 5 hours, cooled to room temperature, and ground to obtain a chlorosilicate cyan long afterglow luminescent material (Sr 7.785 SiO 12 Cl8: Eu 0.015 , Tm 0.2 ).

[0039] The XRD spectrum of the cyan long afterglow luminescent material prepared in Example 2 is as follows: Figure 1 As shown. It can be seen from the figure that this long afterglow luminescent material is a very good single-phase sample, and there is no obvious impurity peak. The chromaticity coordinates of the cyan long afterglow luminescent material obtained in Example 2 were calculated using the CIE chromaticity diagram: x=0.1312, y=0.2664, which is located in the cyan luminescent area. The cyan long afterglow luminescent material obtained in Example 2 has two traps, with peak values ​​at 121°C and 268°C, respectively. The afterglow time is about 4 hours (after irradiation with a 254nm wavelength ultraviolet lamp for 10 minutes, the light source is removed), and the luminous brightness is 0.07759cd / m 2 .

[0040] Example 3

[0041] According to the chemical formula Sr 7.939 SiO 12 Cl8: Eu 0.03 ,Gd 0.006 , Dy 0.025 The raw materials were transferred into a mortar, and an appropriate amount of alcohol was added, ground and mixed to obtain a raw material mixture. The raw material mixture was placed in an alumina crucible, transferred to a high-temperature tube furnace, and introduced into a reducing atmosphere composed of 15% H2 and 85% N2 by volume. The mixture was calcined at 800°C for 3 hours, cooled to room temperature with the furnace, and ground to obtain a chlorosilicate cyan long afterglow luminescent material (Sr 7.939 SiO 12 Cl8: Eu 0.03 , Gd0.006 , Dy 0.025 ).

[0042] The XRD spectrum of the cyan long afterglow luminescent material prepared in Example 3 is as follows: Figure 1 As shown in the figure, it can be seen that this long afterglow luminescent material is a very good single-phase sample, and no obvious impurity peak appears. Under the excitation of ultraviolet light with a wavelength of 350nm, the emission spectrum of the cyan long afterglow luminescent material obtained in Example 3 shows a broadband emission centered at 483nm, which is Eu 2+ The characteristic emission of 5d-4f, such as Figure 4 As shown. The chromaticity coordinates of the cyan long afterglow luminescent material obtained in Example 3 were calculated using the CIE chromaticity diagram: x=0.1301, y=0.2559, which are located in the cyan luminescent region. The cyan long afterglow luminescent material obtained in Example 3 has two traps, with peak values ​​at 68°C and 272°C, respectively. The afterglow time of this long afterglow luminescent material exceeds 5 hours (after irradiation with a 254nm wavelength ultraviolet lamp for 10 minutes, the light source is removed), and the initial brightness of the luminescence is 0.06953cd / m 2 ,like Figure 5 shown.

[0043] Example 4

[0044] According to the chemical formula Sr 7.972 SiO 12 Cl8: Eu 0.02 , Nd 0.008 The stoichiometric ratio was 1.1769 g of SrCO3, 0.3124 g of H2SiO3, 0.4279 g of NH4Cl, 0.0035 g of Eu2O3 and 0.0013 g of Nd2O3, respectively. The raw materials were transferred to a mortar, and a proper amount of alcohol was added for grinding and mixing to obtain a raw material mixture. The raw material mixture was placed in an alumina crucible, transferred to a high-temperature tube furnace, NH3 was introduced, calcined at 1000°C for 5 hours, cooled to room temperature with the furnace, and ground to obtain a chlorosilicate cyan long afterglow luminescent material (Sr 7.972 SiO 12 Cl8: Eu 0.02 , Nd 0.008 ).

[0045] The XRD spectrum of the cyan long afterglow luminescent material prepared in Example 4 is as follows: Figure 1As shown in the figure, it can be seen that this long afterglow luminescent material is a very good single-phase sample, and no obvious impurity peak appears. The chromaticity coordinates of the cyan long afterglow luminescent material obtained in Example 4 are calculated using the CIE chromaticity diagram: x=0.1310, y=0.2684, which is located in the cyan luminescent region. The cyan long afterglow luminescent material obtained in Example 4 has three traps, and the peaks are located at 57°C, 114°C and 250°C, respectively. Figure 6 The afterglow time of this long afterglow luminescent material exceeds 4 hours (after irradiation with a 254nm UV lamp for 10 minutes, the light source is removed), and the initial brightness of the luminescence is 0.00834cd / m 2 .

[0046] Example 5

[0047] According to the chemical formula Sr 7.91 SiO 12 Cl8: Eu 0.04 , La 0.05 The raw materials were transferred into a mortar, and a proper amount of alcohol was added for grinding and mixing to obtain a raw material mixture. The raw material mixture was placed in an alumina crucible, transferred into a high-temperature tube furnace, and introduced into a reducing atmosphere composed of 20% CO and 80% N2 by volume. The mixture was calcined at 900°C for 4 hours, cooled to room temperature, and ground to obtain a chlorosilicate cyan long afterglow luminescent material (Sr 7.91 SiO 12 Cl8: Eu 0.04 ,La 0.05 ).

[0048] The XRD spectrum of the cyan long afterglow luminescent material prepared in Example 5 is as follows: Figure 1 As shown. It can be seen from the figure that this long afterglow luminescent material is a very good single-phase sample, and no obvious impurity peak appears. The chromaticity coordinates of the cyan long afterglow luminescent material obtained in Example 5 were calculated using the CIE chromaticity diagram: x=0.1310, y=0.2684, which is located in the cyan luminescent area. There are three traps in this long afterglow luminescent material, with peak values ​​at 57°C, 120°C and 268°C respectively. Among them, the thermoluminescence peaks at 57°C and 120°C are conducive to the generation of afterglow at room temperature. In complete darkness, the afterglow time of the cyan long afterglow luminescent material obtained in Example 5 can be maintained at 0.00032cd / m 2 About 6 hours above (after irradiation with 254nm UV light for 10 minutes, remove the light source), Figure 7 As shown, the initial brightness of the light is 0.07852cd / m 2 .

[0049] Example 6

[0050] According to the chemical formula Sr 7.92 SiO 12 Cl8: Eu 0.015 , Ho 0.025 , Er 0.04 The raw materials were transferred into a mortar, and a proper amount of alcohol was added for grinding and mixing to obtain a raw material mixture. The raw material mixture was placed in an alumina crucible, transferred into a high-temperature tube furnace, and introduced into a reducing atmosphere composed of 20% H2 and 80% N2 by volume. The mixture was calcined at 900°C for 6 hours, cooled to room temperature, and ground to obtain a chlorosilicate cyan long afterglow luminescent material (Sr 7.92 SiO 12 Cl8: Eu 0.015 , Ho 0.025 , Er 0.04 ).

[0051] The XRD spectrum of the cyan long afterglow luminescent material prepared in Example 6 is as follows: Figure 1 As shown. It can be seen from the figure that this long afterglow luminescent material is a very good single-phase sample, and no obvious impurity peak appears. The chromaticity coordinates of the cyan long afterglow luminescent material obtained in Example 6 are calculated using the CIE chromaticity diagram: x=0.1308, y=0.2687, which is located in the cyan luminescent area. The cyan long afterglow luminescent material obtained in Example 6 has three traps, with peak values ​​at 57°C, 111°C and 250°C, respectively. The afterglow time exceeds 3 hours (after irradiation with a 254nm wavelength ultraviolet lamp for 10 minutes, the light source is removed), and the initial brightness of the luminescence is 0.07513cd / m 2 .

Claims

1. A chlorosilicate cyan long afterglow luminescent material, characterized in that: The chemical structure of the cyan long afterglow luminescent material is: Sr 8-m-n SiO 12 Cl8:Eu m , R n ; wherein R is one of La, Tm, Nd; or R is a combination of Gd and Dy; or R is a combination of Ho and Er; 0.001≤m≤0.4, 0.001≤n≤0.

4.

2. A method for preparing the chlorosilicate cyan long afterglow luminescent material according to claim 1, characterized in that: Follow these steps: 1) According to the chemical expression Sr 8-m-n SiO 12 Cl8:Eu m , R n The stoichiometric ratios of the chemical elements in the mixture are as follows: SrCO3 or SrO; SiO2 or H2SiO3; NH4Cl or SrCl2 Eu2O3; One of La2O3, Tm2O3, Nd2O3; or Gd2O3 and Dy2O3; or Ho2O3 and Er2O3; The raw materials are mixed, an appropriate amount of ethanol is added, and the mixture is ground to obtain a raw material mixture; 2) The raw material mixture is placed in an alumina crucible, moved to a high-temperature tube furnace, introduced into a reducing atmosphere, sintered at 800-1100°C for 3-6 hours, cooled to room temperature with the furnace, and ground to obtain a chlorosilicate cyan long afterglow luminescent material.

3. The method for preparing the chlorosilicate cyan long afterglow luminescent material according to claim 2, characterized in that: The reducing atmosphere in step 2) is one of the following three: the first is ammonia; the second is a mixed gas consisting of 5-25% hydrogen and 95-75% nitrogen by volume; the third is a mixed gas consisting of 5-25% carbon monoxide and 95-75% nitrogen by volume.

Citation Information

Patent Citations

  • A pyrosilicate long afterglow luminescent material and its preparation method

    CN107903892B

  • Europium and ytterbium co-doped silicate green light long afterglow material as well as preparation method and application thereof

    CN114958353A